High-Quality Input Choice under Uncertainty and Ambiguity: An Exploratory Study of Costa Rica’s Coffee Sector - Najera, Joselyne; Arzadun, Paula; Navarro, Monica; Solis, Martin (Journal of Economics and Behavioral Studies, 2018)
The purpose of the present study was to analyze the effect of multiple variables on the decision to invest in high versus regular-quality coffee production inputs. Thereby, a laboratory experiment was conducted with one hundred twenty-three undergraduate students, and posterior logistic regressions with random intercept were executed to analyze the collected data. The results showed that when there is a difference in the investment cost between a coffee of higher quality and a coffee of lower quality (regular), there is a slight increase in the odds ratio of investment in quality coffee, when going from an uncertainty condition of income to one with certainty in income of a higher quality coffee. On the other hand, when the cost is equal for both types of coffee, there is a strong increase in the odds ratio when going from an uncertainty condition to one with certainty. In addition, it was found that both the possibility of loss if there is an investment in a higher quality coffee and the ambiguity in the probability of facing a favorable business climate, reduce the odds ratio of investing in higher-quality coffee.